Cr-based sputtered decorative coatings for automotive industry - Carneiro, Edgar Manuel Neto (2021)
The present work aims to study the impact of O and N addition on Cr-sputtered coatings on plastic (polycarbonate, PC) used in automobile parts, as a promisor alternative for auto part metallization, while eliminating the usage of toxic hexavalent chromium. The coatings were deposited using DC magnetron sputtering from a single pure Cr target in a reactive atmosphere (N2 and/or O2). The deposition of the coatings was performed maintaining the total pressure constant and close to 1 Pa by tuning Ar pressure while reactive gases were added. The target current density was kept at JW = 20 mA·cm−2. Structural characterization revealed a mixture of α-Cr, δ-Cr, β-Cr2N, and CrN crystalline structures as well as amorphous oxides. The coating hardness ranged from 9 GPa for the CrON coating to 15 GPa for the CrN coating. All deposited coatings showed a particularly good interface adhesion; adjusting the amount of O and N made it possible to tune the optical properties of the Cr-based coatings as desired. The promising results open future industrialization of sputtered Cr-based coatings for automotive industries.